1998
DOI: 10.1164/ajrccm.158.4.9710087
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Perception of Dyspnea in Patients with Severe Asthma

Abstract: Poor dyspnea perception might be a risk factor for developing asthma exacerbations. We investigated whether severe asthmatics with recurrent exacerbations (brittle asthma) have different dyspnea perception and sputum cells compared with equally severe, but stable asthmatics, or patients with mild steroid-naive asthma. Fifteen brittle asthmatics (13 female, median age 28 yr [range, 20 to 47 yr]), 15 matched severe-stable asthmatics (14 female, median age 26 yr [range, 17 to 52 yr]), and 11 mild asthmatics (8 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
2
11

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 33 publications
(55 reference statements)
5
79
2
11
Order By: Relevance
“…Indeed, there is a weak correlation between symptoms on the one hand and bronchial hyperresponsiveness and airways inflammation on the other. Several investigators have highlighted the possibility of diminished perception of dyspnoea in subjects with more severe grades of asthma, potentially leading to undertreatment in these subjects [7][8][9]. Such an inverse relationship is not a consistent finding [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is a weak correlation between symptoms on the one hand and bronchial hyperresponsiveness and airways inflammation on the other. Several investigators have highlighted the possibility of diminished perception of dyspnoea in subjects with more severe grades of asthma, potentially leading to undertreatment in these subjects [7][8][9]. Such an inverse relationship is not a consistent finding [10].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between dyspnoea perception and other indices of asthmatic severity, such as the degree of bronchoconstriction, is poor [5,6]. Conversely, impaired dyspnoea perception is especially believed to play a role in severe asthma [7][8][9]. Poor perception of airflow obstruction may lead to undertreatment of asthma [10].…”
mentioning
confidence: 99%
“…African-American participants' comments indicated passivity regarding symptoms due to acclimatization to an inability to inhale, chest tightness, weakness, or dyspnea. It is believed that patients with more severe asthma underestimate the severity of their disease because of a blunted perception of dyspnea (15)(16)(17), and many African-Americans in our focus groups were unable to detect or describe when their asthma was worsening. This is particularly worrisome given the highly educated nature of our participants, suggesting that many patients with asthma are not properly taught by their physician about the nature and symptoms of their disease.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the bronchial hyperreactivity tests were performed by experienced lung function assistants, who also had experience with Borg and VAS scores in children. In adults (median age 25 yrs), VEEN et al [27] found a slope of 0.06 for the Borg/FEV1 correlation in adults with brittle asthma and a Borg slope of 0.11 in stable asthma. Thus, the same small differences observed in the present study are found in adult patients with a clinically different asthma presentation.…”
Section: Discussionmentioning
confidence: 99%